Basic Communicative Strategies and Tactics of Russian and Armenian Medical Media Discourse - Petrosyan, M. M. (Diskurs professionalʹnoj kommunikacii, 2024)
This article explores the deployment of various communicative strategies within prominent medical blogs. The study analyzes 400 texts in Russian and Armenian, sourced from diverse social networks. The selection of these materials is justified by the growing popularization of medical knowledge and the escalating public interest in health, which motivates physicians to undertake active educational initiatives across all accessible information platforms. The objective of this research is to systematically delineate the primary communicative strategies and tactics employed in Russian- and Armenian-language medical blogs authored by doctors from a range of specialties. The significance of this study arises from the incontrovertible popularity of social networks and the progressive mediatization of medical discourse, coupled with a gap in scholarly literature regarding the comparative analysis of Russian and Armenian medical discourses. The findings reveal that medical media discourse on social networks predominantly implements two communicative strategies: informational-educational and manipulative. Each strategy has distinct goals and is manifested through specific communicative tactics. The informational-educational strategy seeks to disseminate medical knowledge through tactics such as providing concise information, referencing authoritative sources, offering guidance, and dispelling medical myths. In contrast, the manipulative strategy aims to market certain products or services, thus actively employing marketing tactics like extolling the virtues of one’s offerings, drawing attention to the blogger’s professional accomplishments and expertise, among others. The study concludes that tactics associated with the manipulative strategy are prevalent in both Russian and Armenian medical blogs, as are tactics related to myth debunking, instructional guidance, and the provision of succinct information within the informational-educational framework.